2011
DOI: 10.4315/0362-028x.jfp-10-250
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Methicillin-Resistant Staphylococcus aureus in a Fresh Meat Pork Production Chain

Abstract: The objective of this study was to investigate the prevalence of methicillin-resistant Staphylococcus aureus on different stages of a fresh pork production chain to reveal potential carryover from live animals to meat. Samples were collected at different stages of the production process in a large German abattoir with an integrated processing unit for fresh pork. Samples included nasal swabs from pigs at stunning, environmental samples from the slaughter line, surface samples from carcasses, environmental and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 17 publications
3
57
1
2
Order By: Relevance
“…In our study, in two of the herds (herds 2 and 9), none of the samples taken from pigs on the farm were MRSA positive, whereas MRSA was detected in pigs belonging to same herds sampled at lairage. These data support the findings of previous studies (2,5,29) on the potential role of the environment as a source of MRSA to pigs. We did not sample any of the transportation trucks, lairage, slaughter areas, or personnel associated with transportation and slaughtering of pigs, so it is difficult to draw any conclusion from this study on the role of the environment as a source of colonization of pigs with MRSA during transportation and holding at lairage, carcass, and retail meat contaminations.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In our study, in two of the herds (herds 2 and 9), none of the samples taken from pigs on the farm were MRSA positive, whereas MRSA was detected in pigs belonging to same herds sampled at lairage. These data support the findings of previous studies (2,5,29) on the potential role of the environment as a source of MRSA to pigs. We did not sample any of the transportation trucks, lairage, slaughter areas, or personnel associated with transportation and slaughtering of pigs, so it is difficult to draw any conclusion from this study on the role of the environment as a source of colonization of pigs with MRSA during transportation and holding at lairage, carcass, and retail meat contaminations.…”
Section: Discussionsupporting
confidence: 83%
“…MRSA has previously been detected in swine transportation trucks, at lairage, in slaughter areas, in pork production shower facilities, and from farm and slaughterhouse personnel (2,5,9,22,29). Broens and colleagues (5) followed individual pigs from the farm to slaughter, indicated that many of the pigs that tested MRSA negative on the farm became MRSA positive during transportation from the farm to the slaughterhouse, and suggested that sources of colonization of pigs with MRSA could be mixing of pigs from different farms during the time between loading and stunning, contaminated trucks and lairage, or personnel (including truck drivers and/or slaughterhouse personnel).…”
Section: Discussionmentioning
confidence: 99%
“…From 18 halves, MRSA was only detected in the initial enrichment broth, whereas on one half, MRSA was detected up to 10 −2 dilution of the enrichment broth. The MRSA prevalence (47.5%) determined in our study, which investigated one herd, was higher than the prevalences observed in two other studies, being 6% and 4% of the carcasses (Beneke et al, 2011 andHawken et al, 2013, respectively).…”
Section: Resultscontrasting
confidence: 50%
“…While investigating German pork processing units, Kastrup [139] determined a MRSA detection frequency of 6% on meat trimmings, 2% on processing equipment, and 5% on employees. Beneke et al [152] obtained a similar detection rate in the processing area of a German abatoir. In an experimental seting, S. aureus at a contamination level of 5-7 log CFU/100 cm −2 was detectable on dry stainless steel for at least 96 h. In The Netherlands, de Jonge et al [39] assessed the presence of MRSA in three meat-processing facilities and two institutional kitchens.…”
Section: Mrsa In Food Processing Environmentsupporting
confidence: 52%